The Influence of Brand Trust on the Repurchase Intention in Skin Care Industries - Razati, Girang; Putri, Amanda Sevia; Wibowo, Lili Adi (Journal of Business Management Education (JBME), 2024)
This research aims to find out the impact of Brand Trust on Repurchase Intention. This type of research uses descriptive and verification methods with a quantitative approach. The dependent variables in this study are repurchase intention (Y), and brand trust (X) as independent variables. Populations in this study are Nivea reviewers on Shopee Niveas.Official.Store has a total of 1,700 and a sample of 425 respondents who are Nivea consumers using simple random sampling techniques. The analysis technique used is Simple Linear Regression Analysis with the help of Computer Software SPSS 26.0 for Windows. The findings of this study found that the image of brand trust versus repurchase intention is in a fairly good category. Brand trust has a positive and significant influence on repurchase intention. The findings show that the implementation of brand trust by Nivea will be able to encourage repurchase intention among NIVEA customers in Indonesia.